CARA PANDANG EMPOWERMENT DALAM PROGRAM PADAT KARYA DI DINAS TENAGA KERJA DAN TRANSMIGRASI KABUPATEN KULON PROGO - IMAN AMANDA PERMATASARI (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2021)
Empowerment Discussed in Kulon Progo Regency there is no reference to the Kulon Progo Manpower and Transmigration Office (Disnakertrans), especially in one program that was implemented. The purpose of this study was to determine the perspective of empowerment in a Padat Karya program at the Manpower and Transmigration Office of Kulon Progo Regency. The research method used is qualitative. Meanwhile, the findings in this study are that the Padat Karya program which is claimed as part of empowerment by the Manpower and Transmigration Office of Kulon Progo Regency, in essence, does not fulfill the concept of empowerment. This can be seen from several things, namely: 1) in terms of empowerment of meaning, Padat Karya cannot specifically target certain residents. The target is farmers who are not farming. According to the author, this is not a form of weakness; 2) this program only has two of the three principles of empowerment, namely doing tasks and results; 3) the development orientation of the Intensive Work Referring to economic improvement only, not to the development community through the empowerment of farmers; 4) the concept of sustainability in empowerment cannot be seen, the program will only run if the community has the opportunity to do it, so it is not independent, creative, or innovative.